Do Social Networks Improve Chinese Adults' Subjective Well-being? - Xiaoyan Lei; Yan Shen; James P. Smith; Guangsu Zhou (Institute for the Study of Labor (IZA), 2015)
This paper studies relationships between social networks, health and subjective well-being (SWB) using nationally representative data of the Chinese Population the Chinese Family Panel Studies (CFPS). Our data contain SWB indicators in two widely used variants happiness and life-satisfaction. Social network variables used include kinship relationships measured by marital status, family size, and having a genealogy; ties with friends/relatives/neighbors measured by holiday visitation, frequency of contacts, and whether and value gifts given and received; total number and time spent in social activities, and engagement in organizations including the communist party, religious groups, and other types. We find that giving and receiving gifts has a larger impact on SWB than either just giving or receiving them. Similarly the number of friends is more important than number of relatives, and marriage is associated with higher levels of SWB. Time spent in social activities and varieties of activities both matter for SWB but varieties matters more. Participation in organization is associated with higher SWB across such diverse groups as being a member of the communist party or a religious organization. China represents an interesting test since it is simultaneously a traditional society with long-established norms about appropriate social networks and a rapidly changing society due to substantial economic and demographic changes. We find that it is better to both give and receive, to engage in more types of social activities, and that participation in groups all improves well-being of Chinese people.
Keywords: O10; O53; 330; China; social networks; subjective well-being